Taxonomic reorganization of family Partitiviridae and other recent progress in partitivirus research - Nibert, Max L.; Ghabrial, Said A.; Maiss, Edgar; Lesker, Till; Vainio, Eeva J.; Jiang, Daohong; Suzuki, Nobuhiro (Virus research, 2014)
•Family Partitiviridae has undergone a taxonomic reorganization.•Four new genera of fungal or plant partitiviruses have been added to the family.•The three former genera of fungal or plant partitiviruses have been eliminated.•Other recent progress of note in partitivirus research is summarized.•Partitivirus effects on their hosts appear not to be cryptic in many cases. Phylogenetic analyses have prompted a taxonomic reorganization of family Partitiviridae (encapsidated, bisegmented dsRNA viruses that infect plants, fungi, or protozoa), the focus of this review. After a brief introduction to partitiviruses, the taxonomic changes are discussed, including replacement of former genera Partitivirus, Alphacryptovirus, and Betacryptovirus, with new genera Alphapartitivirus, Betapartitivirus, Gammapartitivirus, and Deltapartitivirus, as well as redistribution of species among these new genera. To round out the review, other recent progress of note in partitivirus research is summarized, including discoveries of novel partitivirus sequences by metagenomic approaches and mining of sequence databases, determinations of fungal partitivirus particle structures, demonstrations of fungal partitivirus transmission to new fungal host species, evidence for other aspects of partitivirus–host interactions and host effects, and identification of other fungal or plant viruses with some similarities to partitiviruses. Some outstanding questions are also discussed.